Carbon Dots/Cu2O Composite with Intrinsic High Protease‐Like Activity for Hydrolysis of Proteins under Physiological Conditions. (16th September 2018) - Li, Bin; Chen, Daomei; Nie, Minfang; Wang, Jiaqiang; Li, Yizhou; Yang, Yepeng
Abstract: Whereas a variety of inorganic nanomaterials possessing intrinsic peroxidase‐like activity have recently attracted considerable interest, little attention is given to explore their intrinsic protease‐mimic activities. And the construction of efficient enzyme mimetics for the hydrolysis of peptide bonds in proteins still represents a major technical challenge due to the high stability of peptide bonds and the importance of proteases in biology and industry. Herein, it is described for the first time that Cu2 O‐decorated carbon quantum dots (CQDs/Cu2 O) possess an intrinsic protease‐mimic activity to hydrolyze proteins including bovine serum albumin (BSA) and casein under physiological conditions. CQDs/Cu2 O also features a desirable stability and good reusability. CQDs/Cu2 O has a much higher affinity for BSA than trypsin. To the best of knowledge, this is the first example of protein hydrolysis by stable composite nanomaterials under physiological conditions which may open this catalytic system for a multitude of potential applications in biological systems. Abstract : A protease‐mimic material based on Cu2 O‐decorated carbon quantum dots composite nanomaterials is provided, which possesses excellent hydrolysis of proteins (bovine serum albumin and very stable casein) under physiological conditions over a broad temperature range.